2018
DOI: 10.1111/tpj.13996
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous and non‐autonomous functions of the maize Shohai1 gene, encoding a RWPRK putative transcription factor, in regulation of embryo and endosperm development

Abstract: In plants, establishment of the basic body plan during embryogenesis involves complex processes of axis formation, cell fate specification and organ differentiation. While molecular mechanisms of embryogenesis have been well studied in the eudicot Arabidopsis, only a small number of genes regulating embryogenesis has been identified in grass species. Here, we show that a RKD-type RWP-RK transcription factor encoded by Shohai1 (Shai1) is indispensable for embryo and endosperm development in maize. Loss of Shai1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
(142 reference statements)
2
6
0
Order By: Relevance
“…Mutation of OS1 results in unbalanced nutrient allocation between endosperm and embryo in maize kernels. A similar finding was also recently reported for the same gene (Mimura et al 2018).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Mutation of OS1 results in unbalanced nutrient allocation between endosperm and embryo in maize kernels. A similar finding was also recently reported for the same gene (Mimura et al 2018).…”
supporting
confidence: 91%
“…Mutation of OS1 results in unbalanced nutrient allocation between endosperm and embryo in maize kernels. A similar finding was also recently reported for the same gene (Mimura et al ). Dek42 is a new gene, encoding an RRM_RBM48 type RNA binding protein, and mainly functions in intron‐alternative splicing particularly for the U12‐type introns (Zuo et al ).…”
supporting
confidence: 91%
“…The most widely used is maize B-A chromosome translocation, which is able to produce a genetically nonconcordant endosperm and embryo in one kernel (Sheridan and Neuffer, 1980;Beckett, 1994). Utilizing this approach, one can observe a defective embryo rescued by a normal endosperm, indicating that a few genes expressed in the endosperm nonautonomously modulate embryo development and that normal embryo development requires a functional endosperm (Fouquet et al, 2011;Mimura et al, 2018). The second approach is by means of the rare heterofertilization phenomenon, in which the genetic relatedness between the endosperm and embryo influences embryo development (Wu et al, 2013).…”
Section: Maize Zein-rnai Knockdown Mutants As a Novel System To Studymentioning
confidence: 99%
“…By contrast, embryo development relies on a functional endosperm, and severe impairment during early endosperm development usually leads to nonviable or small embryos (Kang et al, 2008;Sosso et al, 2015). Some defectiveembryo mutations can be rescued by a wild-type endosperm via maize B-A chromosome translocations and even by in vivo culture (Sheridan and Neuffer, 1980;Fouquet et al, 2011;Mimura et al, 2018). Thus, impaired nutrient transfer and signal communication between the endosperm and embryo, as well as homozygous mutations of the embryo, can be responsible for defects manifest in the embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that EAS-specific gene expression could be a result of several independent factors, some of which could originate from the endosperm, and others from the embryo. The mechanisms involved in embryo cavity formation remain elusive, although a recent study showed that the SHOHAI1 protein is required in the endosperm for the formation of the embryo cavity (Mimura et al, 2018).…”
Section: The Importance Of the Embryo For The Expression Of Eas Markementioning
confidence: 99%